Pelatihan Pendidikan Entrepreneurship Bagi Siswa-Siswi SMAK Frateran: Penentuan Strategi Harga Jual - Gunawan, Lenny; Agustiono, Agustiono; Hongdiyanto, Charly; Hartono, Wendra (Jurnal Leverage, Engagement, Empowerment of Community (LeECOM), 2021)
The purpose of this community service to Frateran Highschool is to increase their understanding towards Determining Pricing Strategy within their businesses. This training is on live discussion via zoom regarding the previous experiences in determining pricing strategy among lecturers, facilitators, and students as participants. These activities were conducted in an hour meeting session on 17th September 2021, as community service from Ciputra lecturers’ activity to SMAK. Frateran Surabaya. The class was attended by 12 out of 15 students registered, grade XII within Entrepreneurship Subject. The pricing strategies matrix consists of 3x3 quadrants, which then divided into 1. Fixed menu Pricing, and 2. Dynamic Pricing. Students also learned about value added within a product, thus lead them into positioning and differentiation for the businesses. The explanation also given by using examples for each method: Traveloka, Gofood, Grabfood (promotional posters & vouchers) to balance out peak and low order times, Ovo (program features in application) increasing customers convenience in adding values, Starbucks (personnel contribution service and behind the scenes operational video). The conclusion, the activity was able to increase students’ understanding of fixed and dynamic pricing strategy, value added within products/services, and finally positioning and differentiation within service industry.